IMPROVING STUDENTS’ SPEAKING PERFORMANCE BY USING TALKING STICK METHOD - Ananda, Elsa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This research was conducted based on the problems found in the process of learning activities.. The purpose of this research was to improve students’ speaking performance by using talking stick method. This classroom action research was conducted in 3 cycles. The participant of this research was 14 students of the second grade of SMPS BumiKhatulistiwa in Academic Year 2016/2017. The data were gathered from observation-checklist, field note and students’ score in each cycle. The data showed that the students’ were encouraged to speak confidently in front of their friends.In the cycle 1, the main problem faced by the students was they did not use various vocabularies. In the cycle 2, the students were enthusiastic to speak; tell their experience even they still used limited vocabulary to describe their opinion. Then, in the cycle 3, only small number of students who had problem in their performance, almost all students had improved their performance. In conclusion, the implementation of talking stick method could encourage students to speak and also helped the students solve their problems in speaking; self-confident. Keywords: Talking stick method, Students speaking performance. Abstrak: Penelitian ini dilaksanakan berdasarkan masalah yang ditemukan didalam proses pembelajaran. Tujuan dari penelitian ini adalah untuk meningkatkan kemampuan siswa untuk tampil berbicara dengan menggunakan metodologi tongkat berbicara. Penelitian tindakan kelas ini dilaksanakan dalam 3 siklus. Peserta dari penelitian adalah 14 orang siswa dari kelas delapan SMPS Bumi Khatulistiwa tahun akademik 2016/2017. Data menunjukkan bahwa siswa terdorong untuk berbicara dengan percaya diri didepan teman-temannya. Di siklus 1, masalah yang sering dihadapi siswa adalah mereka tidak menggunakan kosakata yang beragam. Di siklus 2, siswa-siswa telah antusias untuk berbicara; menceritakan tentang pengalaman mereka walaupun mereka masih menggunakan kosakata yang terbatas untuk mendeskripsikan opini mereka. Lalu, di siklus 3, hanya sedikit dari mereka yang masih memiliki masalah di penampilan mereka. Hampir seluruh siswa telah melakukan peningkatan.Kesimpulannya, penerapan metode tongkat berbicara dapat memicu siswa untuk berbicara dan juga membantu siswa untuk memecahkan masalah mereka dalam berbicara yaitu kepercayaan diri. Kata kunci : Metode tongkat berbicara, Penampilan berbicara siswa.